(untitled) (Research, Society and Development, 2020)
The objective of this work was to characterize the in natura semen of the native Brycon amazonicus species from refrigeration tests with undiluted semen and diluted in four different solutions. Breeding males from fish farming were used. Milt was frozen and stored in dry shippers immediately after collection. The analyzed parameters were: volume of semen, concentration, pH, motility time and motility rate. The diluents tested were Ringer, Glucose, Sucrose and NaCl. The mean values obtained were: volume = 426.6 μL, concentration = 5.7 x 106spzmL-1, pH = 7.5, motility time = 56.6s and motility rate = 98%. Among the treatments tested, two groups with significant differences were observed: 1) with high motility rate, composed by treatments with undiluted semen and Ringer; 2) with low motility rate and very close to 30%, consisting of NaCl and Glucose treatments. The motility time of B. amazonicus pure semen was maintained up to 96 hours after dilution, indicating that this taxon has a good potential for fish farming.